Improvement in functional performance of people suffering from brain stroke — the role of a nurse - Grochulska, Agnieszka; Jastrzębska, Maria (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Introduction. Advances in medical knowledge and technology are considered important factors that are able to prolong life in individuals with damages of a nervous system. The number of the handicapped people suffering from brain stroke has been constantly increasing. That is why a proper and constant rehabilitation remains a crucial issue. Complexity of neurological and functional deficits make physiotherapeutic treatment conditional upon compensation of defects and recovering process. Nowadays we are aware that the results of brain stroke might be reversible, thus rehabilitation treatment should be flexible and properly adjusted to the patients needs. Therefore various forms of treatment should meet the individual needs of patients and the effects of treatment should be constantly evaluated and verified by interdisciplinary teams. Aim of the study. The aim of the study was to evaluate improvement in functional performance and independence in performing basic activities of people suffering from brain stroke after they were admitted to the hospital up to 4-6 weeks of introducing a complex therapeutic process. Another purpose of the research was to collect information which functions were regained in the first stages of recovery. Material and methods. The research included randomly selected 75 patients suffering from brain stroke hospitalized in the Neurology and LUM Ward of Voivodeship Specialist Hospital in Słupsk. Evaluation of functional condition and patient’s ability to perform everyday activities was based on Barthel index, that allowed to estimate a level of patients independence in performing particular activities on the scale from 0 to 100 points. Results and conclusions. Every third respondent suffering from brain stroke after a period of 6 weeks did not complain and was able to perform everyday activities. The most difficult tasks were showering and bathing while eating and moving in and out from bed to chair were fairly easy. Only effective functioning of an interdisciplinary team considerably improves quality of treatment and care provided to patients and their relatives.